A note on the identification of dynamic economic models with generalized shock processes - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2013)
DSGE models with generalized shock processes have been a major area of research in recent years. In this paper, I show that the structural parameters governing DSGE models are not identified when the driving process behind the model follows an unrestricted VAR. This finding implies that parameter estimates derived from recent attempts to estimate DSGE models with generalized driving processes should be treated with caution, and that there exists a tradeoff between identification and the risk of model misspecification.
Keywords: C13; C32; E00; 330; identification; DSGE models; observational equivalence; maximum likelihood